2021
DOI: 10.1111/iju.14528
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an educational program for medical staff in preventing incidents related to Foley catheter insertion and maintenance: A single‐institution retrospective study

Abstract: To analyze incidents related to Foley catheter insertion and maintenance, and to compare the rate of incidents before and after a medical staff education program. Methods: Data regarding Foley catheter insertion incidents and maintenance were collected at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…15 Conversely, more recent study by Komiya et al showed no improvements in symptomatic UC trauma following UC educational programming. 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Conversely, more recent study by Komiya et al showed no improvements in symptomatic UC trauma following UC educational programming. 14…”
Section: Discussionmentioning
confidence: 99%
“…15 Conversely, more recent study by Komiya et al showed no improvements in symptomatic UC trauma following UC educational programming. 14 Separately, various nursing protocols and algorithms have also been proposed. For example, a recent study suggested a "1 gentle attempt only" rule for junior health care professionals after analyzing a cohort of UC injuries in which there were 3.2 attempts on average before urological consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation